Predicting Land Use and Land Cover Changes for Landscape planning: an integration of Markov chains and Cellular automata using GIS - Gutierres, F. (2021)
The spatial dynamics of landscapes are the consequence of a multiplicity of relations among physical, biological and social forces. So, it is essential the assessment of the driving forces related to Land Use and Land Cover changes (LULC) to understand the change process. The stochastic modeling technique in Geographical Information System (GIS) - Markov Chain (MC) analysis and Cellular Automata (CA) allows the predictions of future changes based on changes that have occurred in the past. This chapter aims to present a dynamic simulation model for LULC changes in ‘Sado Estuary’ and ‘Comporta-Galé’ Natura 2000 Sites (Portugal) for the beginning of the second half of the XXI century by using MC and CA. Regarding the quantification of the fragmentation processes and LULC changes in ‘Sado Estuary’ and ‘Comporta- Galé’ Natura 2000 Sites, these models are able to reveal non-obvious trends in the data and to describe ecological patterns. From an applied research point of view, this approach is useful to identifying adequate planning and management strategies for coastal ecosystems, for monitoring and planning natural and protected environments.